Rekam Jejak Bahasa Arab: Fushah, Amiyah, dan Lahjah dalam Perspektif historis - Nuraini, Ayat; Hasibuan, Renni (Prodi. Pendidikan Bahasa Arab, 2024)
A deep understanding of the differences between Fushah, Amiyah, and various Lahjah varieties in Arabic is essential for grasping the linguistic and cultural richness of the Arab world. This research aims to explore the distinctions between Classical Arabic (Fushah) and Colloquial Arabic (Amiyah), as well as the regional dialects (Lahjah) used among Arab communities. Through a literature review, the researcher conducts an in-depth analysis of books and journal articles addressing this topic, followed by synthesis to draw conclusions. This study is expected to contribute to enhancing understanding of Arabic language specifically. The findings indicate significant differences among Classical Arabic, Colloquial Arabic, and regional dialects in terms of usage and scope. Classical Arabic, as the formal standard, is generally used in official communication and formal writing such as the Quran and scholarly literature. Conversely, Colloquial Arabic is used informally in everyday communication among communities. Regional dialects, as variations of dialect, emerge from specific environments with differences in pronunciation, vocabulary, and grammar. Classical Arabic has served as a strong foundation throughout the history of the Arabic language, playing a key role in various forms of expression and remaining relevant as a valuable cultural heritage for the Arab and Islamic world at large.